2020
DOI: 10.1021/acs.nanolett.0c00376
|View full text |Cite
|
Sign up to set email alerts
|

Long Range Energy Transfer in Self-Assembled Stacks of Semiconducting Nanoplatelets

Abstract: Fluorescent emitters like ions, dye molecules or semiconductor nanoparticles are widely used in opto-electronic devices, usually within densely-packed layers. Their luminescence properties can then be very different from when they are isolated, because of short-range interparticle interactions such as Förster resonant energy transfer (FRET). Understanding these interactions is crucial to mitigate FRET-related losses and could also lead to new energy transfer strategies. Exciton migration by FRET hopping betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…Figure S12b in the Supporting Information demonstrates that the emission from the top layer at 650 nm is intense in the absence of a separator (red) but weak for large separations (20 nm, black) (Figure S12b, Supporting Information). As expected for LR-FRET, [37,38,45,46] the energy transfer occurs over rather far distances of >10 nm, which are substantially longer than those in normal FRET processes (see Figure S11, Supporting Information, showing fluorescence life-time quenching for the c-HL sample).…”
Section: Resultssupporting
confidence: 59%
“…Figure S12b in the Supporting Information demonstrates that the emission from the top layer at 650 nm is intense in the absence of a separator (red) but weak for large separations (20 nm, black) (Figure S12b, Supporting Information). As expected for LR-FRET, [37,38,45,46] the energy transfer occurs over rather far distances of >10 nm, which are substantially longer than those in normal FRET processes (see Figure S11, Supporting Information, showing fluorescence life-time quenching for the c-HL sample).…”
Section: Resultssupporting
confidence: 59%
“…[26][27][28] However, while interlayer transfer of charge carriers is inefficient, excitons can potentially transfer efficiently from one layer to another through dipole-dipole coupling. [29][30][31] Dipole-dipole coupling in layered perovskites is expected to be particularly strong as these materials exhibit large oscillator strengths (> 10 Debye) and favorable dipole alignment. 32 To date, energy transfer studies in 2D perovskites have been focused exclusively on films of mixed dimensionality, studying the transfer between phases of distinct layer thickness (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…47 Finally, we have shown that the origin of this ultrafast timescale lies beyond conventional Forster theory, and adds to similar observations of energy transfer in other 2D systems. 30,48 Further studies will be needed to elaborate the details of the underlying physics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, columnar self‐assembled NPLs emit polarized light due to the dominant presence of in‐plane transition dipole orientations. [ 41 ] Due to the close distance between neighboring NPLs in the stacked films, the observation of ultrafast fluorescence resonance energy transfer (FRET) was uncovered by several groups, [ 44–49 ] which also leads to accelerated nonradiative Auger recombination (AR) processes accounting for the more efficient exciton trapping by nonemissive trapped NPLs during carrier transfer. Until then, only edge‐up orientation of assembled CdSe NPLs with peripheral side contact with the substrate had been accomplished.…”
Section: Introductionmentioning
confidence: 99%